Importance of coccolithophore‐associated organic biopolymers for fractionating particle‐reactive radionuclides (234Th, 233Pa, 210Pb, 210Po, and 7Be) in the ocean. Issue 8 (18th August 2017) - Lin, Peng; Xu, Chen; Zhang, Saijin; Sun, Luni; Schwehr, Kathleen A.; Bretherton, Laura; Quigg, Antonietta; Santschi, Peter H.
Abstract: Laboratory incubation experiments using the coccolithophore Emiliania huxleyi were conducted in the presence of 234 Th, 233 Pa, 210 Pb, 210 Po, and 7 Be to differentiate radionuclide uptake to the CaCO3 coccosphere from coccolithophore‐associated biopolymers. The coccosphere (biogenic calcite exterior and its associated biopolymers), extracellular (nonattached and attached exopolymeric substances), and intracellular (sodium‐dodecyl‐sulfate extractable and Fe‐Mn‐associated metabolites) fractions were obtained by sequentially extraction after E. huxleyi reached its stationary growth phase. Radionuclide partitioning and the composition of different organic compound classes, including proteins, total carbohydrates (TCHO), and uronic acids (URA), were assessed. 210 Po was closely associated with the more hydrophobic biopolymers (high protein/TCHO ratio, e.g., in attached exopolymeric substances), while 234 Th and 233 Pa showed similar partitioning behavior with most activity being distributed in URA‐enriched, nonattached exopolymeric substances and intracellular biopolymers. 234 Th and 233 Pa were nearly undetectable in the coccosphere, with a minor abundance of organic components in the associated biopolymers. These findings provide solid evidence that biogenic calcite is not the actual main carrier phase for Th and Pa isotopes in the ocean. In contrast, both 210 Pb and 7 Be were found to be mostly concentrated in the CaCO3 coccosphere, likely substituting for Ca 2+ during coccolith formation. Our results demonstrate that even small cells ( E. huxleyi ) can play an important role in the scavenging and fractionation of radionuclides. Furthermore, the distinct partitioning behavior of radionuclides in diatoms (previous studies) and coccolithophores (present study) explains the difference in the scavenging of radionuclides between diatom‐ and coccolithophore‐dominated marine environments. Key Points: Coccolithophore‐associated organic biopolymers rather than biogenic calcite serve as the main carrier phases for Th/Pa and Po Pb and Be are incorporated into biogenic calcite as a substitution of Ca 2+ during coccolith formation Different patterns of fractionation between radionuclides occur where coccolithophores versus diatom‐dominated systems